Resisting Best-Practice in Australian Practice-Based Jazz Doctorates. Issue 1 (25th October 2016) - Coady, Christopher; Webb, Michael
Abstract : Recent research on practice-based doctorates in Australia has revealed an institutional preference for 'theorised' research approaches aimed at situating studies of practice within established academic paradigms. In this article we examine how the aim of communicating with artistic peers steers the research design and the production of text-based artefacts for a group of practice-based doctoral students working on jazz topics (n = 11) away from theorised approaches and towards what is commonly referred to as a 'commentary' approach. This finding reveals the extent to which the values of an artistic community can influence the scope of what is discussed within practice-based doctorates and highlights the need for ongoing discussion related to how such values might best interface with what institutions view as best-practice research frameworks.